Raformulasi Frasa Sejak Diketahui dalam Peraturan Mahkamah Agung Nomor 1 Tahun 2022 tentang Tata Cara Penyelesaian Permohonan dan Pemberian Restitusi dan Kompensasi Kepada Korban Tindak Pidana - Maharani 'Ainul Qolbi Fadhilah; Arya Bimantara; Rury Elva; Mochammad Awaludin Rizqi Nurhasan (Jurnal Hukum Lex Generalis, 2026)
One legal remedy available to victims of criminal acts to obtain compensation for material and non-material losses is restitution, which can be filed through the public prosecutor during the trial, after a final and binding decision, or through the Witness and Victim Protection Agency (LPSK). Applications must be submitted within 90 days of the victim learning of the final decision. However, the provisions in Supreme Court Regulation Number 1 of 2022 are open to multiple interpretations, particularly the phrase "from the date the plaintiff learned of the decision," potentially creating legal uncertainty. This study aims to examine the implications of this provision and formulate clearer phrasing. The method used is normative juridical based on relevant legal materials to produce a formulation that guarantees legal certainty.